Extraction and Conversion of Microalgal Lipids - Guldhe A.; Singh B.; Ansari F.A.; Sharma Y.; Bux F. (My University, 2025)
Efficient downstream processing is crucial for successful microalgal biodiesel production. Extraction of lipids and conversion of lipids are the main downstream steps in microalgal biodiesel production process. This chapter provides the overview of the conventional as well as novel extraction and conversion technologies for microalgal lipids. The extraction and conversion technologies have to be environmentally friendly and energy efficient for sustainable and economically viable microalgal biodiesel production. © Springer International Publishing Switzerland 2016.